Challenges and Support Systems for Non-Early Childhood Education Teachers in Kindergarten Instruction - Gastador, Cherry; Almerez, Queenie Lyn; Trinidad, Amelie; Fuentes, Augie; Martinez, Dulce Marie (Journal of Interdisciplinary Perspectives, 2025)
This study explored the instructional challenges and support systems encountered by non-Early Childhood Education (non-ECE) teachers in kindergarten settings. Recognizing the increasing deployment of non-ECE graduates in early childhood programs, the study examined how gaps in training, pedagogical alignment, and classroom management affected instructional effectiveness. A qualitative, phenomenological approach was utilized, involving in-depth interviews with twelve non-ECE kindergarten teachers across selected Davao del Sur Division districts. Thematic analysis revealed three significant challenges: professional and pedagogical mismatch, student engagement and behavior management difficulties, and limited familiarity with play-based learning. Teachers employed self-directed learning, multimedia tools, and parental collaboration as coping mechanisms. However, these were often unstructured and insufficient. Findings highlighted the critical need for targeted professional development, structured mentorship, and access to quality instructional resources. Moreover, inconsistencies in parental involvement also affected the continuity of learning. The study recommends strengthening institutional support from the Department of Education and teacher training institutions to enhance early childhood instructional competence among non-ECE teachers. These insights contribute to the broader discourse on quality kindergarten education and the urgent need for inclusive capacity-building efforts in the early childhood teaching workforce.